Articulación, intercambios y necesidad de dineros alternativos en la economía regional. El caso de Cusco - Romero Reyes, Antonio (1997)
This article starts talking about the block and regional subaccumulation, by market and intersectorial relationships, the demographics, social and productive dynamics, such as rural and urban articulation (disarticulation?). Then, the article focus on how the peasant markets goes on, and their credits, in Vilcanota basin like an intermediate region. It's very important to say that in this place the money has many rules and different purposes. There are no difference between the money such a capital in a regional scale and the money just like an exchange way in microregional spaces. It finishes with some conclusions in function of the central objective.